Procedure-related, false-positive cytology results during EUS-guided FNA in patients with esophageal cancer. - van Hemel BM; Lamprou AA; Weersma R; Plukker JTM; Suurmeijer AJH; van Dullemen HM (Gastrointestinal Endoscopy, 2010)
Background: EUS is a standard staging procedure in esophageal cancer. For adequate staging, FNA of suspicious lymph nodes is recommended. Based on optimal staging, sophisticated treatment can be applied more properly. The working channel of the endoscope can potentially be contaminated by cancer cells derived from the luminal surface of esophageal cancer during EUS-guided FNA, which may result in false-positive cytology results of EUS-guided FNA of celiac lymph nodes. Objective: To determine whether passing an endoscope through intraluminal esophageal cancer can lead to contamination of the working channel with tumor cells. Design: An ex vivo assessment of contamination of endoscope working channels. Setting: University hospital. Patients: This study involved 13 patients with esophageal cancer. Intervention: Working channels of endoscopes that had been used in patients with intraluminal esophageal cancer were studied immediately after EUS. A routine ex vivo FNA was performed through the endoscope on 8 patients. The same procedure was performed through the endoscope on 5 other patients after the working channel had been cleaned by extensive flushing. Main Outcome Measurements: Semiquantitative scoring of cytology smears. Results: Six of 8 specimens contained carcinoma cells. No contamination by carcinoma cells or normal cells was observed when the working channel was flushed with tap water prior to the sham FNA procedure. Limitations: This was an ex vivo study of a limited group of patients. Conclusion: The working channel of the endoscope can be contaminated during the EUS-guided FNA procedure. Cancer cell contamination can be avoided by flushing the endoscope.